معيقات مشاركة تلميذات المرحلة الثانوية في الأنشطة الرياضية المدرسية - بن قسمي يعقوب; لباد معمر (University of Eloued جامعة الوادي, 2024)
نهدف من خلال هذه الدراسة إلى التعرف على المعيقات التي تحول دون مشاركة تلميذات المرحلة الثانوية في الأنشطة الرياضية المدرسية وهذا من وجهة نظر تلميذات المرحلة الثانوية، ولتحقيق ذلك استخدم الباحثان المنهج الوصفي التحليلي لمعرفة وجهة نظر التلميذات حيال هاته المعيقات من خلال تصميم استبانة لجمع البيانات تم تقسيمها إلى ست محاور، وقام الباحثان بالاعتماد على العينة العشوائية حيث تم توزيع (340) استبانة استرجع منها(300) بنسبة استجابة بلغت حوالي(75%). ولتحقيق هدف الدراسة قام الباحثان باستخدام عدة أساليب إحصائية منها ألفا كرونباخ للتأكد من الثبات، والتكرارات والنسب المئوية لوصف متغيرات الدراسة، والوسط الحسابي لتحديد مستوى الإجابة على متغيرات الدراسة. وأظهرت نتائج الدراسة أنه لا توجد فروق في نظرة التلميذات نحو جميع المعوقات قيد الدراسة. حيث كانت إجاباتهم على أن المعوقات المرتبطة بالإمكانيات الرياضية والمرتبطة بالجانب الديني هي الأكثر تأثيرا حيث احتلت المراتب الأولى مما جعلها تكون سببا رئيسيا في عدم مشاركتهن في الرياضة المدرسية وتليها المعيقات الأخرى.وبناءا على نتائج الدراسة تم التقدم بالعديد من التوصيات التي كان أهمها ضرورة توفير ما يلزم لممارسة الأنشطة الرياضية في المدارس مثل إنشاء قاعات رياضية مغلقة واعتماد ميزانية كافية لشراء الأدوات والأجهزة الرياضية اللازمة لممارسة الأنشطة الرياضية وكذلك ضرورة تفعيل دور الأندية الرياضية داخل المدارس والتركيز على فئة الإناث. Abstract: The aim of this study is to identify the obstacles that prevent secondary school girls students from participating in school sports activities, and this is from the point of view of secondary school girls ’ students . To achieve this, the researchers used the analytical descriptive approach to find out the students' point of view about these obstacles by designing a questionnaire to collect data that was divided into six chapters. The researchers relied on the random sample, where (340) questionnaires were distributed, of which (300) were retrieved, with a response rate of about (75%). To achieve the aim of the study, the researchers used several statistical methods, including Cronbach's Alpha to ensure stability, frequencies and percentages to describe the study variables, and the arithmetic mean to determine the level of response to the study variables. The results of the study showed that there were no differences in the students' view of all the obstacles under study, Where their answers were that the obstacles related to sports capabilities and related to the religious aspect were the most influential, as they occupied the first ranks, which made them a major reason for their non-participation in school sports, followed by other obstacles. Based on the results of the study, many recommendations were made, the most important of which was the need to provide what is necessary for practicing sports activities in schools, such as establishing closed sports halls and adopting a sufficient budget to purchase the sports tools and devices necessary for practicing in sports activities, as well as the need to activate the role of sports clubs within schools and focus on the female category
Keywords: معيقات; تلميذات مرحلة ثانوية; أنشطة رياضية مدرسية; obstacles; secondary school girls; School sports activities